Evaluation of Austrian pine (Pinus nigra) plantations in Hungary with respect to nature conservation – a review - Cseresnyés, Imre; Tamás, Júlia (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
The review deals with the stands of the alien Austrian pine (Pinus nigra Arn.) in Hungary, emphasizing the ecological consequences of the afforestation. A short historical overview about the establishment of pine cultures is presented with outlining the distribution of the stands among the major forestry regions of Hungary. The nature conservation and economic problems associated with Austrian pine are summarized, including: the local extinction of the species-rich native flora, the less valuable timber, the rapid physiological decay of trees followed by pathogen epidemics, the insufficient soil amelioration effect, as well as the special vulnerability to forest fires and non-native plant invaders. Applicability of the conifer for land reclamation purposes is also introduced. Finally, we describe some directives and proposals concerning the alteration of Austrian pine plantations to native woody associations complying with the sustainable forest management policy.
Keywords: alien tree; forest fire; invasive species; land reclamation; nature conservation; Pinus nigra; sustainable forest management